DNA polymerase catalysis in the absence of Watson-Crick hydrogen bonds: Analysis by single-turnover kinetics - Potapova, Olga (2006)
We report the first pre-steady-state kinetic studies of DNA replication in the absence of hydrogen bonds. We have used nonpolar nucleotide analogues that mimic the shape of a Watson-Crick base pair in order to investigate the kinetic consequences of a lack of hydrogen bonds in the polymerase reaction catalyzed by the Klenow fragment of DNA Polymerase I from Escherichia coli. With a thymine isostere lacking hydrogen bonding ability in the nascent pair, the efficiency (k(pol)/K(d)) of the polymerase reaction is decreased by 30-fold, affecting ground state (K(d)) and transition state (k(pol)) approximately equally. When both thymine and adenine analogues in the nascent pair lack hydrogen bonding ability, the efficiency of the polymerase reaction is decreased by about 1000-fold, with most the decrease attributable to the transition state. Reactions using nonpolar analogues at the primer terminal base pair demonstrated the requirement for a hydrogen bond between the polymerase and the minor groove of the primer-terminal base. The R668A mutation of Klenow fragment abolished this requirement, identifying R668 as the probable hydrogen bond donor. Detailed examination of the kinetic data suggested that Klenow fragment has an extremely low tolerance of even minor deviations of the analogue base pairs from ideal Watson-Crick geometry. Consistent with this idea, some analogue pairings were better tolerated by Klenow fragment mutants having more spacious active sites. By contrast, the Y-family polymerase Dbh was much less sensitive to changes in base pair dimensions, and more dependent on hydrogen bonding between base-paired partners.